STUDIES ON THE CHEMICAL ANALYSIS OF APHID SEMIOCHEMICALS FROM APHIS GOSSYPII (GLOVER) AND APHIS NERII (BOYER DE FONSCOLOMBE) - RUCHIKA KATARIA; DOLLY KUMAR (International Journal of Pharma and Bio Sciences, 2015)
The aphids, Aphis gossypii (Glover) and Aphis nerii (Boyer de Fonscolombe) are serious pests in the agricultural fields of Vadodara, India. In an attempt to find the solutions to reduce the infestations by these pests, behavioral bioassays (using Y-tube olfactometer) were conducted under laboratory conditions. The volatile extracts were extracted through n- hexane solvent from the females of Aphis gossypii and Aphis nerii. Usually aphids secrete both alarm and sex pheromones and it is quite difficult to scan the males in the life cycle because males were found on the secondary host and once in a year. So, my observations will reveal the rate of repulsion of female aphids towards the female volatile extracts which was isolated by both Confinement and Adsorbent methods. The result showed the presence of semiochemicals as an alarm pheromone in the female volatile extract which could repel its own species and other species while it attracts the predators and other associated natural enemies. Upon further study the isolation and identification of volatile extract by using GC-MS showed the presence of a mixture of sesquiterpene compounds such as E-β-farnesene. Hence the information contained in this paper should pave the way to the identification of proper management practices to maximize lure methods. It would also be useful in providing good scope for the further development of ecofriendly methods to control the aphid infestation.